2019
DOI: 10.2147/opth.s227629
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient-Reported Outcomes/Satisfaction and Spectacle Independence with Blended or Bilateral Multifocal Intraocular Lenses in Cataract Surgery</p>

Abstract: Purpose: To compare patient-reported outcomes (PROs) and satisfaction results after multifocal intraocular lens (IOL) implantation in three groups: two receiving bilateral implantation of the same IOL and another undergoing blended vision with two different multifocal IOLs. Patients and methods: A questionnaire was administered to patients who had undergone uncomplicated cataract surgery and 2 months of follow-up: the first group underwent bilateral implantation with Alcon's AcrySof ReSTOR 3.0 lens ("3.0/3.0,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…Our previous work compared PROs, satisfaction rates, and spectacle independence between blended or bilateral multifocal IOLs in patients who underwent cataract surgery (AcrySof IQ ReSTOR +2.5 D and ReSTOR +3.0 D, Alcon, Ft. Worth, Texas). 15 We found that the combination of a ReSTOR +2.5 D and ReSTOR +3.0 D resulted in higher patient satisfaction rates for intermediate vision than bilateral ReSTOR +3.0 D implants, but that overall PRO differences were not statistically significant.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our previous work compared PROs, satisfaction rates, and spectacle independence between blended or bilateral multifocal IOLs in patients who underwent cataract surgery (AcrySof IQ ReSTOR +2.5 D and ReSTOR +3.0 D, Alcon, Ft. Worth, Texas). 15 We found that the combination of a ReSTOR +2.5 D and ReSTOR +3.0 D resulted in higher patient satisfaction rates for intermediate vision than bilateral ReSTOR +3.0 D implants, but that overall PRO differences were not statistically significant.…”
Section: Introductionmentioning
confidence: 66%
“…Comparison was made to two previous cohorts of multifocal IOL patients who had undergone similar surgery and responded to a similar questionnaire in a similar time frame. 15 In that study, the 2.5 mini-monovision cohort received the AcrySof IQ ReSTOR ActiveFocus +2.5 D or AcrySof IQ ReSTOR ActiveFocus +2.5 D add toric implant bilaterally, with the dominant eye targeted for emmetropia and the nondominant eye targeted for −0.5 sphere. The “2.5/3.0” cohort was implanted with the AcrySof IQ ReSTOR ActiveFocus +2.5 D implant in the dominant eye and the AcrySof IQ ReSTOR +3.0 D multifocal lens the nondominant eye.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the present time, there have been marked improvements in achieving uncorrected visual acuity at all distances due to the availability of new trifocal IOL designs. [2][3][4][5][6] With the introduction of new IOL technology, the new IOLs are now able to provide a better enhanced depth of focus as compared to previous multifocal or accommodating IOLs. As a result, this has led to improved visual acuity at all distances, better contrast sensitivity, along with a decrease in both halos and glare symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…As only a part of the light used for image generation is sharp, there is a loss of contrast, which is noticeable. In addition, undesirable optical side effects in the form of so-called halos or glare occur, which impair vision, especially at twilight and at night [5,8]. There is no ideal correction for all distances, but through objective measurement using the Visual Behavior Monitor (VBM) regarding distance measurement, ambient lighting and head posture will potentially determine a much more accurate setting and support the choice of IOL.…”
Section: Introductionmentioning
confidence: 99%